Revisiting India’s Neighborhood First Policy in the Context of Growing US China Engagement in Nepal - Lamichhane, Dron Prasad (Nepal Public Policy Review, 2023)
Where does India’s Neighborhood First policy stand in the context of U.S.-China’s growing strategic engagement in Nepal? It has been realized that Indian Prime Minister Narendra Modi's Neighborhood First Policy was unable to deliver on its economic and developmental promises in a multifaceted manner. Mr. Modi’s initial engagements with Nepal were perceived as accommodating policies, and it was believed that they would bring about a “paradigm shift” that would replace the “Nehru Doctrine.” However, going against the spirit of the speech delivered by Mr. Modi in Nepal’s Constituent Assembly, India imposed an unofficial blockade that pulled down Nepal-India relations. Further, Kalapani border disputes and Mr. Modi’s unwillingness to receive the EPG report also added to the trust deficit. The EPG report was expected to reactivate the trust. However, this vacuum gives the U.S. and China an opportunity to increase their strong presence in Nepal. China’s interest in getting access to South Asia via the BRI project overlaps with the MCC. So, their rivalry to create strategic space in Nepal is going on. On the one hand, India has not joined BRI and believes it String of Pearls strategy. Further, the country perceives any development in the Himalayan region as a security threat. On the other hand, India and the U.S. are global allies since China’s takeover of Tibet and they have held similar views on Nepal. Considering the growing bipolar strategic rivalry between China and the U.S., this paper examines where India’s Neighborhood First policy stands and what the state of its implementation will be. This study uses qualitative, exploratory research techniques to analyze the geopolitical relation and diplomacy.